2022
DOI: 10.1007/s12185-022-03305-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to COVID-19 vaccination in patients with lymphoma

Abstract: Patients with lymphoma are at increased risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); therefore, evaluation of SARS-CoV-2 vaccination efficacy is essential. We conducted a prospective observational study to monitor the antibody response in 500 patients with lymphoma after SARS-CoV-2 vaccination. Antibody levels increased in a stepwise manner after the first and second dose of the vaccine. After completion of the two-dose series, anti-S antibody was negative in 109 patients (21.8%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Most of them were enrolled in our previous cohort investigating humoral response following the initial vaccination series and were compared to HCs. 6 , 7 The dataset was closed on 20 August 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Most of them were enrolled in our previous cohort investigating humoral response following the initial vaccination series and were compared to HCs. 6 , 7 The dataset was closed on 20 August 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Pooled seroconversion rates of hematologic malignancy patients with treatment and those without treatment were calculated from studies with disaggregated data on treatment. 95,109,121,134,137,154,168], subgroup analysis showed significantly lower seroconversion rates in patients receiving allogeneic HSCT (76.7%; 95% CI, 71.6-81.1%, I 2 = 58%) compared to those receiving autologous HSCT (86.3%; 95% CI, 80.5-90.6%, I 2 = 43%), (P = 0.011).…”
Section: Seroconversion Rate and Association With Treatment Modalitiesmentioning
confidence: 95%
“…In addition, we found that no other factors examined, including patient age and blood cell counts, were associated with seropositivity in our cohort, whereas previous studies suggested the relationship between white blood cell count; lymphocyte counts, including CD4-positive T cells and CD19-positive B cells; and the efficacy of COVID-19 vaccine in patients with lymphoma. 10 , 12 , 15 One of the conceivable reasons for these discrepancies might be the difference in the patient population analyzed, as the study by Narita included not only BCLs but also T-cell lymphomas and Hodgkin lymphoma, whereas the study by Perry included patients who were subjected to watch and wait without receiving anti-CD20 MoAb treatment. Tanguay et al pointed out that a peripheral B-cell count of <50/µL was a risk factor for poor antibody production after the COVID-19 vaccine, although this finding was not always related to prior anti-CD20 MoAb treatment.…”
Section: Discussionmentioning
confidence: 99%